Multi-component prime-boost Chlamydia trachomatis vaccination regimes induce antibody and T cell responses and accelerate clearance of infection in a non-human primate model - Lorenzen, Emma; Contreras, Vanessa; Olsen, Anja W.; Andersen, Peter; Desjardins, Delphine; Rosenkrands, Ida; Juel, Helene Bæk; Delache, Benoit; Langlois, Sebastien; Delaugerre, Constance; Joubert, Christophe; Dereuddre-Bosquet, Nathalie; et al. (Frontiers in Immunology, 2022)
It is of international priority to develop a vaccine against sexually transmitted Chlamydia trachomatis infections to combat the continued global spread of the infection. The optimal immunization strategy still remains to be fully elucidated. The aim of this study was to evaluate immunization strategies in a nonhuman primate (NHP) model. Cynomolgus macaques (Macaqua fascicularis) were immunized following different multi-component prime-boost immunization-schedules and subsequently challenged with C. trachomatis SvD in the lower genital tract. The immunization antigens included the recombinant protein antigen CTH522 adjuvanted with CAF01 or aluminium hydroxide, MOMP DNA antigen and MOMP vector antigens (HuAd5 MOMP and MVA MOMP). All antigen constructs were highly immunogenic raising significant systemic C. trachomatis-specific IgG responses. In particularly the CTH522 protein vaccinated groups raised a fast and strong pecificsIgG in serum. The mapping of specific B cell epitopes within the MOMP showed that all vaccinated groups, recognized epitopes near or within the variable domains (VD) of MOMP, with a consistent VD4 response in all animals. Furthermore, serum from all vaccinated groups were able to in vitro neutralize both SvD, SvE and SvF. Antibody responses were reflected on the vaginal and ocular mucosa, which showed detectable levels of IgG. Vaccines also induced C. trachomatis-specific cell mediated responses, as shown by in vitro stimulation and intracellular cytokine staining of peripheral blood mononuclear cells (PBMCs). In general, the protein (CTH522) vaccinated groups established a multifunctional CD4 T cell response, whereas the DNA and Vector vaccinated groups also established a CD8 T cells response. Following vaginal challenge with C. trachomatis SvD, several of the vaccinated groups showed accelerated clearance of the infection, but especially the DNA group, boosted with CAF01 adjuvanted CTH522 to achieve a balanced CD4/CD8 T cell response combined with an IgG response, showed accelerated clearance of the infection